Perinatal taurine exerts a hypotensive effect in male spontaneously hypertensive rats and down-regulates endothelial oxide nitric synthase in the aortic arch - Mensegue, Melisa F. (2020)
Fil: Mensegue, Melisa F. University of Buenos Aires. Institute of Medical Research A. Lanari; Argentina